Between the Lion Cub of Judea and the British Lion: cause lawyers, British rule and national struggle in Mandatory Palestine. Issue 1 (2nd January 2019) - Blum, Shimon-Erez
Abstract : The tempestuous political environment of the final days of British Mandate rule in Palestine saw intensive activity by cause lawyers. As a test case of this activity, this article examines the conduct of the attorneys who handled the case of Dov Gruner, a member of the Irgun Zionist underground. In April 1946, Gruner was sentenced to death by a British military court. Informed by cause lawyering paradigm, the article examines the tactics used by his lawyers and their relations with players within and outside the court. This examination sheds light on the links between nationality, the law and lawyers at that time in Palestine. In particular, the analysis highlights the key role played by the lawyers in the Gruner affair, similar from that perspective to the dominant role of lawyers in the Irish War of Independence and different from the relatively marginal role played by lawyers in Indian freedom struggle.